Formal finance and household enterprise performance in Ghana: The gender dimension - Peng, Yiqing; Adjasi, Charles Komla Delali (Frontiers in Psychology, 2022)
In this study, we empirically examine the gender dimension of the effect of formal finance on enterprise performance. While the literature suggests that formal finance, in general, improves firm performance, this effect may differ across firms headed by male and female entrepreneurs since the latter are faced with more severe social, economic, and financial constraints, which undermine their firm performance. Consequently, the effect of finance on firm performance is expected to be weaker in female-headed enterprises. So far, there is little evidence as to whether a gender gap exists regarding the effect of formal finance on firm performance, especially among small household enterprises. To fill the gap in the literature, we use the Ghana Living Standards Survey 2016/2017 and study the effect of formal credit on the productivity of male-headed and female-headed non-farm household enterprises in Ghana. Our results show that a positive effect of formal credit on labor productivity is only found in male-headed enterprises, but not in female-headed ones. We suspect that this result may be explained by women’s relatively less endowment in conditional factors, such as skills, knowledge, experiences, and capabilities.